In vitro activities of beta-lactam-beta-lactamase inhibitor combinations against Stenotrophomonas maltophilia: correlation between methods for testing inhibitory activity, time-kill curves, and bactericidal activity. - Muñoz Bellido, J L (1997)
The activities of ampicillin, ampicillin-sulbactam, amoxicillin, amoxicillin-clavulanic acid, ticarcillin, ticarcillin-clavulanic acid, piperacillin, piperacillin-tazobactam, aztreonam, and aztreonam-clavulanic against Stenotrophomonas maltophilia strains for which the MICs of penicillins and commercially available beta-lactam-beta-lactamase inhibitor combinations were higher than the breakpoints usually recommended for Pseudomonas aeruginosa in commercially available broth microdilution methods were tested by the agar diffusion, agar dilution, and broth microdilution methods. Time-kill curve studies were performed when discrepancies between these methods were observed. The MICs obtained by the commercially available broth microdilution method, the agar dilution method, and the broth microdilution method were almost identical. Twenty-five percent of the strains tested showed inhibition diameters of > or =15 mm for ticarcillin-clavulanic acid, and 43.7% of the strains tested showed inhibition diameters of > or =18 mm for piperacillin-tazobactam by the agar diffusion method. The time-kill curves for these strains confirmed the results obtained by dilution methods. Aztreonam-clavulanic acid (2:1) at concentrations of < or =16 microg/ml inhibited all of these strains (MIC range, 1 to 16 microg/ml). The time-kill curves confirmed this activity. The addition of piperacillin to this combination did not modify the MICs. The combination aztreonam-clavulanic acid-ticarcillin was two- to fourfold more active than aztreonam-clavulanic acid alone. We studied the inhibitory and bactericidal activities of the two most active combinations (aztreonam-clavulanic acid and aztreonam-clavulanic acid-ticarcillin) against the standard inoculum and 10 and 50 times the standard inoculum. Inoculum modifications did not modify the MICs. Both combinations showed good bactericidal activity against the standard inoculum. With 10 times the standard inoculum, minimum bactericidal concentration (MBC) results were heterogeneous (for 55% of the strains, MBCs were between the MIC and 4-fold the MIC, and for 45% of the strains MBCs were between 8- and >32-fold the MIC). With 50 times the standard inoculum, MBCs were at least 32-fold the MICs for all the strains tested.